Kajian Manajemen Transportasi Untuk Perencanaan Ekowisata Bukit Watu Belah di Kalurahan Banjarasri Kapanewon Kalibawang: Study of Transportation Management for Bukit Watu Belah Ecotourism Planning in Kalurahan Banjarasri Kapanewon Kalibawang - Dhony P. S.; Amrita Winaya; Aris Krisdiyanto; Kemmala Dewi (Jurnal Suara Pengabdian 45, 2023)
This community service activity aims to identify the existing conditions of the location that is planned to become a tourist village, in the form of outreach so that the Government of Kalurahan Banjarasri Kapanewon Kalibawang can find out a general description to plan an ecotourism, especially in the scope of transportation management. The method of activities carried out to achieve the goals of Community Service (PPM) are surveys, observations, planning and outreach as well as discussions from the community service team to Kalurahan Banjarasri officials. There are two alternatives routes to Bukit Watu Belah, and from the observations it is known that the second alternative route has a road width varying from 1,5 to 5 meters. Pavement of this village’s main road is asphalt while the road to the top of the hill is still a dirt road. In terms of transportation, the new “Bukit Watu Belah” ecotourism is worth continuing, with an ecogreen feeder transportation concept for 4-wheeled vehicles or buses.